Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Assessing Pleistocene–Holocene climatic and environmental change in insular Near Oceania using stable isotope analysis of archaeological fauna - Patrick Roberts; Sean Hixon; Rebecca Hamilton; Mary Lucas; Jana Ilgner; Sara Marzo; Stuart Hawkins; Sindy Luu; Chris Gosden; Matthew Spriggs; Glenn Summerhayes (Journal of Quaternary Science, 2023)
In comparison to temperate and arid regions, environmental responses to the Last Glacial Maximum and the Terminal Pleistocene and Holocene boundary remain poorly known for many parts of the tropics, making it challenging to unravel human–landscape interactions across this timeframe. This is particularly the case in insular Near Oceania, where sea‐level fluctuations and potential changes in forest cover may have had major impacts on hunter–gatherer populations. Here, we apply stable carbon and oxygen isotope analyses to small‐mammal teeth from four Pleistocene–Holocene (spanning from 29 000 years ago to the late Holocene) sequences in the Bismarck Archipelago to reconstruct changes in environments directly exploited by human populations in this part of the world. Our results show a subtle response of tropical habitats in Near Oceania to relatively arid conditions during the late‐glacial period, something that has also been observed at sites in South and Southeast Asia, followed by a Terminal Pleistocene–Holocene expansion of tropical forest cover. Nevertheless, site‐based variability in environmental responses across this period highlight the need for more multidisciplinary studies of human occupation sequences in a region that is becoming increasingly central to exploring human adaptations, environmental modifications and social network development over the past 20 000 years.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Taphonomy of bird (Aves) remains at Laili Cave, Timor-Leste, and implications for human-bird interactions during the Pleistocene - Stuart Hawkins; Sue O’Connor; Julien Louys (Archaeological and Anthropological Sciences, 2019)

Evaluating the relative conservation value of fully and partially protected marine areas - Marija Sciberras; Stuart R Jenkins; Rebecca Mant; Michel J Kaiser; Stephen J Hawkins; Andrew S Pullin (Fish and Fisheries, 2015)
The establishment of marine protected areas ( MPA s), particularly of no‐take areas, is often viewed as a conflict between conservation and fishing. Partially protected areas ( PPA s) that restrict some extractive uses are often regarded as a balance between biodiversity conservation and socio‐economic viability. Few attempts have been made to generalize the ecological effects of PPA s. We synthesized the results of empirical studies that compared PPA s to (i) no‐take reserves ( NTR s) and (ii) to open access ( O pen) areas, to assess the potential benefits of different levels of protection for fish populations. Response to protection was examined in relation to MPA parameters and the exploitation status of fish. Our syntheses suggest that while PPA s significantly enhance density and biomass of fish relative to O pen areas, NTR s yielded significantly higher biomass of fish within their boundaries relative to PPA s. The positive response to protection was primarily driven by target species. There was a large degree of variability in the magnitude of response to protection, although the size of the PPA explained some of this variability. The protection regime within the PPA provided useful insights into the effectiveness of partial MPA s. We conclude that MPA s with partial protection confer advantages, such as enhanced density and biomass of fish, compared to areas with no restrictions, although the strongest responses occurred for areas with total exclusion. Thus, MPA s with a combination of protection levels are a valuable spatial management tool particularly in areas where exclusion of all activities is not a socio‐economically and politically viable option.

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

First record of Skrjabingylus petrowi (Nematode: Metastrongyloidea) in a pine marten Martes martes from Ireland - Peter Stuart; Conall J. Hawkins; D. P. Sleeman; Colin Lawton (European Journal of Wildlife Research, 2010)

Determinants of reproductive potential and population size in open populations of Patella vulgata - Andreas Sundelöf; Stuart R. Jenkins; Carl J. Svensson; Jane Delany; Stephen J. Hawkins; Per Åberg (Marine Biology, 2010)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Population resistance to climate change: modelling the effects of low recruitment in open populations - Carl Johan Svensson; Stuart R. Jenkins; Stephen J. Hawkins; Per berg (Oecologia, 2005)